RELASI LEKSIKAL DAN PROPERTI MAKNA DALAM NASKAH FILM THE BEST EXOTIC MARIGOLD HOTEL - MONGI, DIODORA CHRISTIN NATALIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œLexical Relations and Meaning Properties in The Best Exotic Marigold Hotel Movie Scriptâ€. The objectives of this research are to describe the types of lexical relations and meaning properties and to analyze which type of lexical relations and meaning properties that occur the most in the movie script. This research uses a descriptive method. There are three steps to finish this research, the first step is preparation. In this step, the writer watches the movie to find out the data. The second step is data collection. The writer collects the words that include in lexical relations and meaning properties and compares them with the movie script. The third step is data analysis. The writer describes and classifies the types of lexical relations according to Palmerâ€™s (1976:57-81) theory and meaning properties according to Leechâ€™s (1981:29) theory, then the writer uses formula to get the types that occur the most in the movie script. The results of this research show that there are 72 data include in lexical relations and 107 data include in meaning properties. All of the words according to Palmerâ€™s (1976:57-81) and Leechâ€™s (1981:29) theory are found in this movie. The lexical relations and meaning properties found in the movie script of The Best Exotic Marigold Hotel are 3 data or 5 % of hyponym, 11 data or 19 % of synonym, 23 data or 39 % of antonym, 20 data or 34 % of polysemy, 2 data or 3,3 % of homonym, 103 data or 96 % of meaningfulness, 0 data or 0% of anomaly, 0 data or 0 % of contradictory, 4 data or 3,5% of ambiguity, and 0 data or 0 % of redundancy. It also shows that the types that occur the most are antonym and meaningfulness. The findings of this research support the theory of Palmer and Leech. Â  Keywords : Lexical Relations, Meaning Properties, Movie: The Best Exotic Marigold Hotel; Palmer, Leech.